Poéticas domésticas y otras manualidades - Ponte Guzman, Marilú Maura (2024)
This project seeks to expand the limits of artistic exploration to recognize in the domestic space possibilities of essay and creation, putting into dialogue traditional practices assigned to the female gender with contemporary languages and resources. It proposes a reflection on female subjectivity modeled by the social mandate that exclusively attributes to it the execution of the duties of reproduction and care. The methodology used is artistic exploration, from the field of visual arts, which goes together with writing and the search for references related to the problem and materialities explored. It is a multimedia sculptural installation in which the author appropriates elements (practices, materialities and instruments) of the domestic space, to unload them from their initial function and refer them to the sensations, emotions and tensions typical of coexistence. It makes use of techniques associated with crafts, home care (weaving, darning, sewing, washing) and contemporary visual language (videos and installations) to build a set of six sculptural pieces that are connected to each other, by their origin, for having been extracted from private space, for the techniques used and the sensations they generate. The progress achieved for four of the six components of the project will be shown.